MANAGEMENT OF UROSEPSIS COINCIDENT WITH HYPERTHYROIDISM: A CASE REPORT - Papeo, Dizky Ramadani Putri; Marhaba, Zulkarnain; Upara, Nana Nurindah; Yusuf, Siti Rahmatia; Az-zahra, Vivilia; Delia, Faizha Putri; Kuengo, Gerrald Hariyawan (JURNAL WIDYA MEDIKA, 2026)
Urosepsis is a life-threatening infection originating from the urinary tract and can trigger systemic inflammation. The presence of hyperthyroidism can worsen the prognosis due to increased metabolic rate and hemodynamic instability. This case reports a 54-year-old man who presented to the emergency department with generalized weakness since the previous day, accompanied by nausea without vomiting and intermittent fever that appeared one month after being discharged from the hospital. The patient was subsequently diagnosed with urosepsis with comorbid hyperthyroidism, indicating that the urinary tract infection had progressed to sepsis, further complicated by the pre-existing thyroid condition. Combination therapy with meropenem, levofloxacin, propylthiouracil, and propranolol with supportive therapy showed improvement in clinical condition and laboratory parameters, including a decrease in the leukocyte count and normalization of body temperature. Multidisciplinary management involving infection control and thyroid regulation was effective in stabilizing the patient's condition. This case report aims to describe the management of urosepsis in a patient with comorbid hyperthyroidism using the SOAP approach as a clinical summary.